Thermal and Microstructure Analysis of Cocofoam Made from Blended Coconut Fiber with Latex Compound - Anom, I. D. K.; Setiaji, Bambang; Trisunaryanti, Wega; Triyono (International Coconut Community Journal, 2013)
Thermal and microstructure analysis of cocofoam made from vulcanized coconut fiber and latex compound were conducted. The cocofoam was produced by blending coconut fiber and latex compound with weight ratio of 10/25 (CF5-1) and 20/55 (CF5-2) at room temperature. The cocofoam characters were then analyzed by Scanning Electron Microscope (SEM), Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DTA) instruments. The result showed that the increase of coconut fiber and latex compound ratio produced a higher density of cocofoam. The highest value density was 0.6920 g/cm3 with flexibility of 90% produced by the CF5-2 sample. The SEM analysis showed that both specimens surface of the CF5-1 and CF5-2 samples have different pores size and the latex compound is not distributed thoroughly in the cocofoam. The thermal analysis showed that the production of cocofoam was largely determined by latex compound that served as fiber binder matrix. Cocofoam started to degrade at the temperature of 90°C and was damaged when it was heated at the temperature of 115°C for 2.5 hours.